Clinicopathological Features and Treatment Outcomes in Ewing’s Sarcoma Patients: A 10‑year experience of Alexandria Clinical Oncology Department - Nazeer, Asmaa; Kandil, Alaa; Zahra, Omar; Soliman, Maher (Indian Journal of Medical and Paediatric Oncology, 2017)
Background: Ewing's sarcoma (ES) is an aggressive tumor, which is usually associated with micrometastases in the circulation. Thus, systemic chemotherapy in addition to local control modality is essential to improve outcomes. The aim of this study was to evaluate clinicopathological features and treatment outcomes in patients with ES. Materials and Methods: Medical files of 74 patients with nonmetastatic ES treated at our centers between 2004 and 2014 were retrospectively evaluated. The clinicopathological parameters were extracted and statistically correlated with event-free survival (EFS) and overall survival (OS). Results: The median age of patients was 13 years. The median follow-up duration was 63.8 months. About two-thirds (58.1%) of patients were male. Pain (74.3%) was the most common presenting symptom. Extremities (48.6%) were the frequently affected sites. Thirty-two patients (43.2%) presented by tumors larger than 8 cm. All patients were treated with chemotherapy. Local therapies were surgery and/or radiotherapy. The 5-year EFS and OS were 44% and 57%, respectively. On multivariate analysis, EFS and OS were significantly associated with age, tumor site, and tumor size. Conclusions: Despite limited resources in a developing country, the survival rates of ES are comparable to that in developed countries, and prognostic factors are age, tumor site, and tumor size.
Keywords: Chemotherapy; Ewing's sarcoma; prognosis; survival